Effect of Mineral Admixtures on Mechanical Properties of Concrete with Partially Replacement of Flyash and Ggbs - shalini kumari, Pothunuri; Srinivas Rao, K.; Deepika, Tirumala (International Journal of Engineering and Technology, 2018)
Being humans the usage of concrete is more and more important now a days. Generally many people have dreams to construct their own houses and also government is take up many big projects like construction of dams, bridges etc. This shows us the necessity of production of huge amount of concrete. But for the production of concrete tremendous amount of cement is required, which in turn leads to the release of large amounts of CO2 into the atmosphere during its manufacturing process. It causes adverse effects to the environment. To decrease amount of CO2 and its adverse effects, we partially replaced the cement with mineral admixtures like GGBS and Fly ash. The present study dealt with the mechanical properties of concrete by using various percentages of mineral admixtures with water to binder content ratio 0.4 and M40 grade of concrete.Â Â